Neophyte Skill Judging Corneoscleral Lens Clearance. Issue 3 (March 2016) - Fuller, Daniel G.; Chan, Nancy; Smith, Brenton
ABSTRACT: Purpose: This study examines the accuracy of neophyte clinicians' assessments of central corneal clearance (CCC) of a corneoscleral lens using lens center thickness (CT) as a biometric scale. Methods: A normal participant was fit with a corneoscleral lens on both eyes. Observers (n = 34) from the final semester of their fourth year in optometric clinical training were instructed to estimate the amount of CCC through the approximate geometrical center of the lens using a standardized script which included a photograph identifying various zones. Observer estimates were then compared against anterior segment-OCT (AS-OCT) values obtained during calibration. Results: Mean observer estimates of central corneal clearances were OD 220.5 ± 121.microns (range 50 to 480 microns) and OS 398.0 ± 159.1 microns (range 140 to 800 microns). The mean AS-OCT values were OD 105.5 ± 11.microns (range 84 to 121 microns) and OS 340.8 ± 15.2 microns (range 315 to 362 microns). Mann-Whitney test was statistically significant for comparison of median values OD (177.0; p = 0.001) and OS (260.0; p = 0.012). Conclusions: Neophyte clinicians in the final semester of their fourth year of optometric clinical training tend to significantly overestimate the amount of CCC in a normal subject with declining accuracy as the amount of clearance diminishes. Abstract : Supplemental digital content is available in the text.